2020
DOI: 10.1089/mdr.2020.0037
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Chelators as Carbapenem Adjuvants for Metallo-β-Lactamase-Producing Bacteria: In Vitro and In Vivo Evaluation

Abstract: Infections caused by metallo-b-lactamase (MBL)-producing bacteria are emerging and carry a significant impact on patients' outcome. MBL producers are spread worldwide, both in community and hospital setting, with increasingly reported epidemic clusters and the search for MBL inhibitors is an important topic for public health. MBLs are zinc-dependent enzymes whose functioning can be hampered by zinc chelators. We evaluated the potential of six zinc chelators (disulfiram, nitroxoline, 5-amino-8-hydroxyquinoline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
0
19
0
2
Order By: Relevance
“…Exposure of MBL-producing bacteria to subinhibitory amounts of metal chelators (EDTA or dipicolinic acid, DPA) renders bacteria sensitive to β-lactam antibiotics, supporting the notion that the levels of periplasmic free Zn­(II) are minimally regulated and depend on the availability of extracellular Zn­(II) . The same effect was observed when using N , N , N ′, N ′-tetrakis­(2-pyridylmethyl)­ethylenediamine (TPEN), a specific Zn­(II) chelator, or Chelex-treated media, indicating that inhibition of MBLs is due to a reduction in extracellular Zn­(II) levels and not to a direct interaction of these enzymes with the metal chelators in the periplasmic space. , In this line, Hood et al demonstrated that exposure of A. baumannii to subinhibitory concentrations of TPEN activating the Zur regulon renders this bacterium susceptible to carbapenems despite the up-regulation of ZnuD1 and ZnuD2 located in the outer membrane .…”
Section: Zn(ii) Homeostasis At the Host–pathogen Interface: Stability...mentioning
confidence: 75%
“…Exposure of MBL-producing bacteria to subinhibitory amounts of metal chelators (EDTA or dipicolinic acid, DPA) renders bacteria sensitive to β-lactam antibiotics, supporting the notion that the levels of periplasmic free Zn­(II) are minimally regulated and depend on the availability of extracellular Zn­(II) . The same effect was observed when using N , N , N ′, N ′-tetrakis­(2-pyridylmethyl)­ethylenediamine (TPEN), a specific Zn­(II) chelator, or Chelex-treated media, indicating that inhibition of MBLs is due to a reduction in extracellular Zn­(II) levels and not to a direct interaction of these enzymes with the metal chelators in the periplasmic space. , In this line, Hood et al demonstrated that exposure of A. baumannii to subinhibitory concentrations of TPEN activating the Zur regulon renders this bacterium susceptible to carbapenems despite the up-regulation of ZnuD1 and ZnuD2 located in the outer membrane .…”
Section: Zn(ii) Homeostasis At the Host–pathogen Interface: Stability...mentioning
confidence: 75%
“…96 Zinc chelators have also been proposed as adjuvants to carbapenems for MBL-producing Enterobacterales as they may reduce the zinc available to the MBL active site, thereby impairing the enzyme's ability to hydrolyze carbapenems. 97 One in vivo study showed that a zinc chelator (DMSA) used in combination with a carbapenem significantly reduced bacterial counts in an MBL-producing E. coli murine peritonitis model compared to carbapenems alone. 98 The clinical implications of these findings remain uncertain.…”
Section: Carbapenemsmentioning
confidence: 99%
“…Nine Gram-negative clinical isolates (six Enterobacterales and three non-fermenting bacilli), collected from different Italian hospitals and previously described as MBL-producers ( bla VIM , bla NDM or chromosomally encoded MBLs) were selected on the basis of their serine-ß-lactamases gene contents, in order to study the antimicrobial activity of ATM in combination with old and new BLIs. In four of these isolates (two Escherichia coli , Citrobacter amalonaticus and Klebsiella pneumoniae LC954/14) these genes were already described [ 16 , 17 , 19 ]; the remaining five strains ( E. coli 482483, K. pneumoniae KL 12 SG, Chryseobacterium indologenes LC650/17, Elizabethkingia meningoseptica LC596/11 and Stenotrophomonas maltophilia LC669/17) [ 18 , 20 ] were investigated for this feature as described below. The genotypic characteristics of all strains are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%